2004
DOI: 10.1002/ajmg.b.30044
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequlibrium in the DTNBP1 (dysbindin) gene region and on chromosome 1p36 among psychotic patients from a genetic isolate in Israel: Findings from identity by descent haplotype sharing analysis

Abstract: Several genes have been reported recently to be associated with schizophrenia and bipolar disorder. Because of the complexity of the inheritance of these disorders, there is an urgent need to replicate these findings and to search for additional candidate genes. The study of genetic isolates is a powerful technique that may overcome some of the obstacles caused by genetic heterogeneity and ambiguity of phenotype definition. Identity by descent (IBD) haplotype sharing analysis in these populations may be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…With the same phenotype (DSM-IV psychosis) in our study, we observe a multipoint NPL score of 2.83 (empirical P ¼ .00061) at this location (16 cM from the pter) and observe a peak multipoint NPL of 3.42 (empirical P ¼ 0.00003) at a location 21 cM centromeric to that locus. Since only two previous studies [Kohn et al, 2004;Craddock et al, 2005] had reported weak (non-significant) linkage to this region, the present study provides the first replication of the report by Abecasis et al [2004] of a locus for psychosis at this site. The present study also provided evidence for a gene related to schizophrenia and psychosis in the chromosome 5q35 region.…”
Section: Discussionsupporting
confidence: 71%
“…With the same phenotype (DSM-IV psychosis) in our study, we observe a multipoint NPL score of 2.83 (empirical P ¼ .00061) at this location (16 cM from the pter) and observe a peak multipoint NPL of 3.42 (empirical P ¼ 0.00003) at a location 21 cM centromeric to that locus. Since only two previous studies [Kohn et al, 2004;Craddock et al, 2005] had reported weak (non-significant) linkage to this region, the present study provides the first replication of the report by Abecasis et al [2004] of a locus for psychosis at this site. The present study also provided evidence for a gene related to schizophrenia and psychosis in the chromosome 5q35 region.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, several genes demonstrating strong evidence of association with schizophrenia have been identified (6,7). It has yet to be established whether these are susceptibility genes for schizophrenia in all populations, but association with both dystrobrevin binding protein 1 (DTNBP1), which codes for dysbindin (8), and neuregulin 1 (9) has been subsequently replicated in other samples (10)(11)(12)(13)(14)(15)(16)(17)(18). The involvement of dysbindin in the pathophysiology of schizophrenia is supported by recent findings that its expression is reduced in both the prefrontal cortex (19) and presynaptic hippocampal sites (20) in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…At least 40 family-based or population-based association studies have attempted to replicate this initial finding (summarized in Table 1), although not necessarily in the strict sense of repeating the design and methods of the initial study. One linkage study in an Israeli isolate directly located a risk region for major psychiatric disorders at the DTNBP1 locus (Kohn et al 2004). At least twenty-two association studies supported the associations between DTNBP1 and schizophrenia in different populations, but seven did not.…”
Section: Introductionmentioning
confidence: 99%